Women's life writing and early modern Ireland - Eckerle, Julie A., 1971-; McAreavey, Naomi (Lincoln : University of Nebraska Press, 2019)
"Women's Life Writing and Early Modern Ireland focuses on women writing in and about seventeenth-century Ireland"--
Alice Thornton, Elizabeth Freke, and the remembrances of Ireland / Raymond A. Anselment -- Reading dislocation and emotion in the writings of Alice Thornton, Ann Fanshawe, and Barbara Blaugdone / Anne Fogarty -- The Boyle women and familial life writing / Ann-Maria Walsh -- Life writing in the Boyle family network / Amelia Zurcher -- The politics of honor in Lady Ranelagh's Ireland / Ruth Connolly -- The place of Ireland in the letters of the First Duchess of Ormonde / Naomi McAreavey -- English-Irish social networks in the seventeenth century / Amanda E. Herbert -- Women's letters in the Lyons Collection of the correspondence of William King / Julie A. Eckerle -- Ownership inscriptions and life writing in the books of early modern women / Jason McElligott -- Appendix: Archives and female life writers of early modern Ireland.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on May 01, 2019).
JSTOR
Keywords: English prose literature -- Irish authors -- History and criticism; English prose literature -- Women authors -- History and criticism; English prose literature -- Early modern, 1500-1700 -- History and criticism; English prose literature -- 17th century -- History and criticism; Women and literature -- Ireland -- History -- 16th century; Women and literature -- Ireland -- History -- 17th century; Ireland -- In literature; Prose anglaise -- 17e siècle -- Histoire et critique; Femmes et littérature -- Irlande -- Histoire -- 16e siècle.; Femmes et littérature -- Irlande -- Histoire -- 17e siècle.; Irlande -- Dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; LITERARY COLLECTIONS -- European -- English, Irish, Scottish, Welsh; English prose literature; English prose literature -- Early modern; English prose literature -- Irish authors; English prose literature -- Women authors; Literature; Women and literature; Ireland; 1500-1700; Criticism, interpretation, etc; History